Navigating Religious Moderation in Halal Tourism: Insights from Traditional Leaders in the Lake Toba Caldera, North Sumatra - Daulay, Maraimbang; Sukardi, Imam; Nasution, Ismail Fahmi Arrauf; Miswari, Miswari (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This study uses the concept of religious moderation to analyze the perceptions of traditional community leaders in Lake Toba Caldera, North Sumatra on halal tourism. Toba, Samosir, Humbang Hasundutan, and Dairi are Christian-majority regions designated as priority tourist destinations by the government, with a focus on halal tourism. A qualitative method was used in this study, with interviews with traditional leaders as the primary source, supplemented by interviews with tourists and business actors, as well as observations and literature reviews. The findings, analyzed through the concept of religious moderation, revealed three perspectives on halal tourism: the first group saw it as a form of Islamization, the second had only a vague idea, and the third rejected the term itself due to its discriminatory connotations. Overall, the traditional leaders accepted halal tourism as a service for Muslim tourists but were not comfortable with the term ‘halal tourism’. This study highlights the importance of religious moderation values, with tolerance and national commitment emerging as the key indicators of religious moderation in the region.